Identical constituent compounds in German. (October 2014) - Finkbeiner, Rita
<x xml:space="preserve">Abstract</x> The status of identical constituent compounds (ICCs) (e.g. Künstler-Künstler, 'artist-artist') is discussed controversially in the morphological literature on German. In this paper, it is claimed that ICC formation is a productive word formation pattern in German. In the first part of the paper, I investigate the formal, semantic and pragmatic properties of ICCs in German. Based on this description, I discuss in more detail two conflicting claims about their meaning constitution: the 'prototype reading claim' and the 'context-dependency claim'. I argue that ICCs do not behave differently, in principle, from canonical N+N compounds with respect to context-dependency. Based on a discussion of selected theoretical models of nominal compounds, an approach is sketched that takes into account not only semantic and contextual, but also stored conceptual and experiential knowledge as main sources of knowledge in ICC interpretation. In the second part of the paper, the results of a pilot experimental study are presented in which 40 native speakers were asked to paraphrase a set of context-free German ICCs. The findings clearly indicate that ICCs are systematically interpretable in isolation, with a significant preference for 'prototype' (e.g. Winter-Winter: 'very cold winter') and 'real' readings (e.g. Holz-Holz: 'real wood, not artificial wood').